Penerapan Model Discovery Learning dengan Pemanfaatan Virtual Laboratory untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar Peserta Didik pada Materi Sistem Ekskresi - Khairuna Khairuna*; Hafnati Rahmatan; M Ali Sarong; Supriatno Supriatno; Andi Ulfa Tenri Pada (Universitas Syiah Kuala, 2021)
Practical skills play an important role in learning to achieve maximum learning outcomes. Lack of involvement in skills activities has an impact on learning outcomes achieved by students.This study aims to analyze the improvement of science process skills and student learning outcomes by applying the discovery learning model and the use of a virtual laboratory. The research method was a quasi-experimental design with a pretest-posttest control group design. The population was 165 students of class XI IPA who came from two schools. The research sample was 113 students, 57 experimental group and 56 control group. This research was conducted in MAN 1 and MAS Oemar Diyan Aceh Besar, Aceh, Indonesia. The research was conducted in the even semester of the 2019/2020 Academic Year. The parameters measured were science process skills and learning outcomes, data collection instruments were multiple choice questions with pretest-postest techniques. Science process skills data and learning outcomes were analyzed using parametric statistics using the independent sample t test. The results showed the correlation between science process skills and student learning outcomes was obtained r = 0.842, this indicates that between science process skills and student learning outcomes has a positive corelation with strong interpretation after being taught with the application of discovery learning models and the use of virtual laboratory on excretory system topic